Identifying the extent of AGN outflows using spatially resolved gas kinematics. Issue Volume 15:Issue S359(2020) (March 2019) - Meena, Beena; Crenshaw, D. M.; Fischer, T. C.; Schmitt, Henrique R.; Revalski, M.; Polack, G. E.
Abstract: We present spatially resolved kinematics of ionized gas in the narrow-line region (NLR) and extended narrow-line region (ENLR) in a sample of nearby active galaxies. Utilizing long-slit spectroscopy from Apache Point Observatory (APO)13s ARC 3.5 m Telescope and Hubble Space Telescope ( HST ) we analyzed the strong λ5007 Å [O III] emission line profiles and mapped the radial velocity distribution of gas at increasing radii from the center. We identified the extents of Active Galactic Nuclei (AGN) driven outflows in our sample and determined the distances at which the observed gas kinematics is being dominated by the rotation of the host galaxy. We also measured the effectiveness of radiative driving of the ionized gas using mass distribution profiles calculated with two-dimensional modeling of surface brightness profiles in our targets. Finally, we compared our kinematic results of the outflow sizes with the maximum distances at which the gas is being radiatively driven to investigate whether these outflows are capable of disrupting or evacuating the star-forming gas at these distances.